Knowledge generation in universities - Beatriz Helena Amador Lesmes (Trilogía Ciencia Tecnología Sociedad, 2018)
This paper presents a review of studies conducted in Mexico, Venezuela, Colombia, Spain, Chile, Ecuador, Argentina, Brazil, and Peru about knowledge generation in different universities. The aim is to analyze conceptualizations, criticism, and the influence of public policy trends regarding knowledge generation on the evaluation systems of university professors. Therefore, the content of reflection and research articles was examined to identify different methods and ideas about knowledge generation and the main implications of public policy trends for the role of university professors as creators of knowledge. This analysis also revealed some proposals that enabled to suggest furthering, tensions, gaps, and plans for future research in the field.